Prospects for Integration of Ukrainian Refugees into the German Labor Market: Results of the ifo Online Survey - Tetyana Panchenko (CESifo Forum, 2022)
In the framework of the project of the ifo Center for International Institutional Comparisons and Migration Research 'Adaptation and Survival Strategies of Refugees from Ukraine in Germany: Between Work and Social Help' a quantitative online survey was conducted. This article aims at reconstructing and clarifying the socio-demographic portrait of Ukrainian refugees in Germany in order to assess their potential in the German labor market and the possible burden on the German social system. The focus of this study is also the plans and intentions of Ukrainian refugees in Germany. This study provides insights on how many Ukrainians will stay in Germany, return to Ukraine, or move to another country, and how many are ready to integrate into the German labor market.
Keywords: 330